Contrast-enhanced ultrasound for musculoskeletal applications: a World Federation for Ultrasound in Medicine and Biology position paper - Fischer, Christian; Krix, Martin; Weber, Marc-André; Loizides, Alexander; Gruber, Hannes; Jung, Ernst-Michael; Klauser, Andrea; Radzina, Maija; Dietrich, Christoph F. (Ultrasound in medicine & biology, 2020)
This World Federation for Ultrasound in Medicine and Biology position paper reviews the diagnostic potential of ultrasound contrast agents for clinical decision-making and provides general advice for optimal contrast-enhanced ultrasound performance in musculoskeletal issues. In this domain, contrast-enhanced ultrasound performance has increasingly been investigated with promising results, but still lacks everyday clinical application and standardized techniques; therefore, experts summarized current knowledge according to published evidence and best personal experience. The goal was to intensify and standardize the use and administration of ultrasound contrast agents to facilitate correct diagnoses and ultimately to improve the management and outcomes of patients.